Evaluation and Assessment of Existing Design Codes and Standards for Building Construction: A State of the Art - Abdulqader, Diman N.; Atrushi, Dawood S. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2022)
Building design codes (BDC) are used to control the construction industry in general and building design in particular. The BDC offers the construction sector with a standard language and set of requirements. There are several BDCs developed and utilized for construction purposes throughout the world. Certain design codes are employed in structural design to assure the structure’s health and safety, as well as its cost-effectiveness. It also assures that the structure is sufficiently sturdy to endure all potential climatic conditions, bear its intended load, and is integrated to ensure effective use of building materials and resources. This research aims to compare various building construction design codes to identify and explore the most appropriate standard in terms of safe design, economics, and availability of details. In Kurdistan and different parts of Iraq, many international companies have designed building structures with various codes during the past 20 years. This is a bad condition since the government has no control over the construction of the buildings, which includes both the code and the building materials. There is currently no overview of the design codes in use in Kurdistan, nor is it clear whether they are congruent with what students’ study in institutions.